Characterization Of Precipitates In Structural Niobium Microalloyed Steel By Transmission Electron Microscopy And Analysis By Low Resolution - L. Béjar-Gómez (The Minerals, Metals and Materials Society, 2006)
The aim of this research work is to study and characterize the precipitates in structural microalloyed steel by transmission electron microscopy and analysis by low resolution. Microalloyed steel with niobium was produced by casting in an electrical induction oven of 25 Kg capacity. Carbon content in steel was less than 0.1 % and 0.036% of niobium. Steel was processed thermomechanically; reheated to 1250 °C and hot rolled on a laboratory mill to a 13.0 mm thick plate with a finish rolling temperature of 900ºC and a thickness reduction of 80% . This work shows what precipitates are present in steel, the type of precipitates and their morphology. Analysis by transmission electron microscopy of low resolution was applied to obtain the chemical analysis of precipitates and the matrix. Spectroscopy of dispersive energy (STEM - EDS) was applied to obtain the element profile of precipitates. Particles of precipitates of NbC were found; with cubic morphology and size from 70 to 130 nm, circular morphology and size from 10 to 70 nm, polygonal morphology and size from 10 to 80 nm.